PHYSIOLOGICAL ALTERATIONS IN HEMOLYMPH OF BLAPS SULCATA BEETLE AS AN INDICATOR OF ENVIRONMENTAL POLLUTION EFFECTS - Beltagy, Bassiouni I.; Omar, Gehan A. (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Environmental pollution of air, water, soil and food became a threat for the sustainability of several plant and animal communities and may ultimately threaten the human survival. The present study was carried out to evaluate the effect(s) of some pollutants, namely, Cadmium, Cd; copper; Cu; Iron, Fe, and Lead, Pb, in soil of two different localities on some physiological parameters (Glucose, total protein, total lipid, phospholipid, uric acid (u.a.), cholinesterase, acid phosphatase (ACP), alkaline phosphatase (ALP), alanine aminotransferase (ALT) and aspartate aminotransferase (AST)) in the hemolymph of the beetle Blaps sulcata. The results obtained in the present study showed that location "M" (Moharam Bey botanival garden at the Faculty of Science, Alexandria University, Egypt) could be considered as polluted as compared to the location "R" (reference site at Burg El-Arab, 50Km west of Alexandria). In soil, levels of Fe, Pb, Cu and Cd were significantly elevated in location "M" as compared to the location "R". In addition, the concentrations of all measured parameters in hemolymph of B. sulcata collected from "M" site were found to be lower than reference site this could be due to an increased the previously mentioned pollutants.